1981
DOI: 10.1007/bf01890272
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal leiomyosarcoma — Unusual sites: Esophagus, colon and porta hepatis

Abstract: This paper is based on a retrospective analysis of the radiologic findings of 6 newly proven cases of primary gastrointestinal leiomyosarcomas located in unusual sites. The radiographic and angiographic features of esophageal, colonic, and porta hepatis leiomyosarcomas are described and illustrated. General background information together with a brief review of the literature regarding these lesions are provided. The difficulties encountered in the preoperative diagnosis are explained by the protean and non-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Leiomyosarcomas are most commonly found in the middle or distal third of the esophagus because smooth‐muscle forms the muscularis propria in these parts of the esophagus 5,6 . They originate from the smooth musculature of the esophageal wall and are divided into two major groups: the more common intraluminal polypoid form and the infiltrative, invasive form 1,6–8 . They consist of interlacing whorls of spindle cells with increased mitoses 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyosarcomas are most commonly found in the middle or distal third of the esophagus because smooth‐muscle forms the muscularis propria in these parts of the esophagus 5,6 . They originate from the smooth musculature of the esophageal wall and are divided into two major groups: the more common intraluminal polypoid form and the infiltrative, invasive form 1,6–8 . They consist of interlacing whorls of spindle cells with increased mitoses 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, esophageal leiomyosarcoma has been classified as polypoid in 60 of cases and as infiltrative in 40% 16 . 17 As for the radiographic findings in leiomyosarcoma of the esophagus, Levine et al 15 reported that esophageal leiomyosarcoma has radiographic features similar to those of leiomyosarcoma found elsewhere in the GI tract. Barium studies most commonly revealed large intramural masses that had a marked exophytic component and often contained areas of ulceration or tracking.…”
Section: Discussionmentioning
confidence: 99%
“…They originate from the smooth musculature of the esophageal wall and are divided into two major groups: the more common intraluminal polypoid form and the infi ltrative, invasive form [4,9,10]. The case in this report was the former, polypoid form, and suitable for endoscopic resection.…”
Section: Discussionmentioning
confidence: 87%